2014
DOI: 10.18632/oncotarget.2435
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 promotes angiogenesis through inhibition of miR-1/Endothelin-1 axis in nasopharyngeal carcinoma

Abstract: Emerging evidence clearly indicates that EZH2 plays a crucial role in tumor angiogenesis. However, the role of EZH2 in angiogenesis is still unknown in nasopharyngeal carcinoma (NPC). We here showed that the elevated EZH2 level was closely associated with an aggressive and poor prognostic phenotype, and was positively correlated with microvessel density (MVD) in NPC tissues. Functional studies showed that EZH2 upregulation promoted cell proliferation, migration and tubule formation of endothelial cells, and kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 47 publications
3
41
0
Order By: Relevance
“…The present study showed a significant association of ET-1 expression with the advanced stage of CSCC cases and positive lymph node metastasis. Similarly, high ET-1 expression and higher stages of laryngeal carcinoma were found to be associated in other studies (7,19). This could be explained by the fact that the ET-1/ETAR axis can promote EMT, thus enhancing invasion and metastasis.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The present study showed a significant association of ET-1 expression with the advanced stage of CSCC cases and positive lymph node metastasis. Similarly, high ET-1 expression and higher stages of laryngeal carcinoma were found to be associated in other studies (7,19). This could be explained by the fact that the ET-1/ETAR axis can promote EMT, thus enhancing invasion and metastasis.…”
Section: Discussionsupporting
confidence: 62%
“…It was suggested that EZH2 could affect cancer angiogenesis as it has genes repressor role (7). It helps cancer stem cell self-renewal; cancer stem cells are the seeds of metastatic spread and can differentiate into tumor-associated endothelial cells (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of EZH2 was associated with an advanced clinical stage and increased risk of relapse, and EZH2 served as an independent poor prognostic factor for patients with NPC (3,22). Therefore, ROCK1 may be partially involved in EZH2-induced progression of NPC.…”
Section: Discussionmentioning
confidence: 98%